Transformational Leadership Training for Church Leaders in A Community Engagement Context - Edi Purwanto (Penerbit Goodwood, 2026)
Purpose: This community engagement program aimed to strengthen the leadership capacity of church leaders through transformational leadership training within a local association of church leaders in South Tangerang, Indonesia. Research Methodology: The program was conducted on February 19, 2026, using a hybrid format combining offline and online participation. More than 50 church leaders, including pastors, ministry coordinators and theology students, participated in the study. Training was conducted using a participatory educational approach through lectures, theological reflection, interactive discussions, and case-based dialogue. The materials focused on four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Results: The training improved participants’ understanding of transformational leadership, shifting their perspective from administrative responsibilities to vision-driven, relational, and empowering leadership, while also strengthening collaboration among churches and encouraging shared ministry initiatives. Conclusions: Transformational leadership training can serve as an effective community engagement strategy to enhance leadership capacity in faith-based organizations. Integrating leadership theory with biblical perspectives provides practical guidance for church leaders to manage ministry, foster collaboration, and promote sustainable organizational development. Limitations: The activity involved participants from a limited regional network and relied primarily on qualitative feedback rather than on long-term evaluation. Contributions: This study contributes to community development practices in religious organizations and highlights the importance of leadership education in strengthening faith-based institutions.